REVITALISASI EKONOMI UNTUK MENINGKATKAN PRODUKTIVITAS, NILAI TAMBAH DAN AKSES PASAR BERBASIS KELESTARIAN KAWASAN HUTAN LINDUNG “BUKIT DAUN” DI KABUPATEN REJANG LEBONG - Soengkono -; Anggri Puspita Sari (UNIVED Press, 2014)
oengkono, Anggri Puspita Sari; This study departs from the failure of the Development Community Forests (Judg.) which until now had never been able to open completely and still keep problems lingering. Based on such phenomena, research aims to revitalize the economic potential of the resource-based local economy and protected forest sustainability through appropriate integrated technological innovation to increase productivity, added value and sustainable market access. This research is designed to be completed during the 2 (two) years by combining two approaches, namely, the economic development and economic sustainability of downstream subsystem sub-system upstream agribusiness to protect and preserve the integrity of protected forest ecosystems. To achieve the goal of this research is to use PRA approach (Participatory Rural Appraisal), qualitative, and action (action research). Information obtained through in-depth interview techniques (indept interview), observations, focused group discussions (Focus Group Discussion) and brainstorming (brainstorming) in the classical media. Data analysis was carried out simultaneously with the process of data collection (on going analysis) and the applicable techniques techniques in qualitative penelitihan. Appropriate technology development Model used adapted, arranged with the potential of existing human resources, natural resources, the potential existence of a team of experts, as well as the potential of the existing business environment. Model development is directed to the formation of groups of people of productive coffee farmers, the development of appropriate technology module production of coffee processing and packaging printing business. Community groups geared to business establishment production of coffee processing and packaging printing business through structured training activities, the establishment of business units, business management, coaching and coaching development effort. The research team gave assistance technology consulting, product certification, as well as coaching development marketing. On these activities will also be developed to support business partner role in enterprise development, including support of the Government, employers, and sources of capital. Key words: Revitalization, Economic, Technology, Productivity, Sustainability